ENGAGING LATINOS IN THE DIABETES SELF-MANAGEMENT PROGRAM & PROGRAMA DE MANEJO PERSONAL DE LA DIABETES. (11th November 2018) - Herrera-Venson, A P; Waterman, G; Mendez-Luck, C; Oquendo-Scharneck, M; Davis, D; Nohelia Montoya, C
Abstract: Latinos comprise the fastest growing segment of the older adult population, with over half expected to have type 2 diabetes by age 70. Diabetes self-management programs can effectively reduce complications from poorly controlled diabetes, yet Latinos participate at half the rate compared to a decade ago (23% to 12%). Data on the Diabetes Self-Management Program and its culturally adapted version, Programa de Manejo Personal de la Diabetes, from the National Council on Aging's database show that, compared to other participants, Latinos were significantly younger, less likely to live alone, and had better attendance. Latinos living alone were less likely to complete a program, and those with more chronic conditions were more likely to complete the program. Latinos reported fewer provider referrals for either program, but more often completed the program at a healthcare facility. Together with insights from community-based partners, this session will review best practices for engaging older Latinos.